Importance of the Antarctic Slope Current in the Southern Ocean Response to Ice Sheet Melt and Wind Stress Change. Issue 5 (16th May 2022) - Beadling, R. L.; Krasting, J. P.; Griffies, S. M.; Hurlin, W. J.; Bronselaer, B.; Russell, J. L.; MacGilchrist, G. A.; Tesdal, J.‐E.; Winton, M.
Abstract: We use two coupled climate models, GFDL‐CM4 and GFDL‐ESM4, to investigate the physical response of the Southern Ocean to changes in surface wind stress, Antarctic meltwater, and the combined forcing of the two in a pre‐industrial control simulation. The meltwater cools the ocean surface in all regions except the Weddell Sea, where the wind stress warms the near‐surface layer. The limited sensitivity of the Weddell Sea surface layer to the meltwater is due to the spatial distribution of the meltwater fluxes, regional bathymetry, and large‐scale circulation patterns. The meltwater forcing dominates the Antarctic shelf response and the models yield strikingly different responses along West Antarctica. The disagreement is attributable to the mean‐state representation and meltwater‐driven acceleration of the Antarctic Slope Current (ASC). In CM4, the meltwater is efficiently trapped on the shelf by a well resolved, strong, and accelerating ASC which isolates the West Antarctic shelf from warm offshore waters, leading to strong subsurface cooling. In ESM4, a weaker and diffuse ASC allows more meltwater to escape to the open ocean, the West Antarctic shelf does not become isolated, and instead strong subsurface warming occurs. The CM4 results suggest a possible negative feedback mechanism that acts to limit future melting, while the ESM4 results suggest a possible positive feedback mechanism that acts to accelerate melt. Our results demonstrate the strong influence the ASC has on governing changes along the shelf, highlighting the importance of coupling interactive ice sheet models to ocean models that can resolve these dynamical processes. Plain Language Summary: As the climate warms, the winds over the Southern Ocean (SO) are expected to increase in strength and shift southward and the Antarctic Ice Sheet (AIS) is expected to continue to melt. Both changes alter ocean circulation in the SO. We investigated the impact of these changes on the physical properties and circulation in the SO in a preindustrial control background state using two coupled climate models with different representations of the Antarctic Slope Current (ASC). In both models, we found an inhomogeneous surface response to these changes. The altered wind stress caused warming of the surface in the Weddell Sea, while the freshwater from the AIS caused surface cooling in the rest of the SO. On the West Antarctic shelf, where most of the observed ice‐shelf melting occurs, the models produced very different responses. In one model, the meltwater elicits a strong subsurface cooling response which would act to limit further melt. In the other model, the meltwater causes a strong subsurface warming response which would act to accelerate further melt. The differing representations of the ASC explain this striking disagreement between the two models. Key Points: Antarctic meltwater and projected wind stress change cause surface warming in the Weddell Sea and cooling in the rest of the Southern Ocean The subsurface response on the West Antarctic shelf differs between the models; one yields strong cooling and the other strong warming The mean‐state representation and acceleration of the Antarctic Slope Current is the key process to explaining the differing shelf response